If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 2) + 8y = 0 Reorder the terms: 2(2 + 3x) + 8y = 0 (2 * 2 + 3x * 2) + 8y = 0 (4 + 6x) + 8y = 0 Solving 4 + 6x + 8y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + 6x + -4 + 8y = 0 + -4 Reorder the terms: 4 + -4 + 6x + 8y = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 6x + 8y = 0 + -4 6x + 8y = 0 + -4 Combine like terms: 0 + -4 = -4 6x + 8y = -4 Add '-8y' to each side of the equation. 6x + 8y + -8y = -4 + -8y Combine like terms: 8y + -8y = 0 6x + 0 = -4 + -8y 6x = -4 + -8y Divide each side by '6'. x = -0.6666666667 + -1.333333333y Simplifying x = -0.6666666667 + -1.333333333y
| (2x+2)+(3x+1)+x=180 | | 2x^2+9=-12x | | P-21=3p-91 | | 7=10-0.1x | | 6x+11-4x+21=2 | | B=2B-66 | | -3(1X+2)+1x=2(1x+2)-10-4x | | 7/2(h-39) | | 663/6= | | 2n^2+11=-10n | | 7/8/14 | | 5b+3-7b=-1 | | 2x+x=301 | | Y+20=2y-40 | | 7x+15=4x+27 | | 2x^2+11=-10n | | 7p=7(5p+7) | | 3x-16i=12+(2y)i | | (8y-2)+(6y+6)=158 | | p+40=6p | | 5(n+2)-3(3n-5)=12 | | 5x^2-54=3x | | 9B=B+24 | | 11g+h=-5 | | 4.22-0.14x=5x-2.205 | | -7x+3(x+4)=8 | | 23/9*3 | | -24+2m=-22 | | 7k^2-20=-10k | | 14/18=42/? | | -2(v-2)=-4v-4 | | 12+24=-36t |